Pengaruh Model Pembelajaran Kooperatif Tipe Think Pair Share (TPS) terhadap Hasil Belajar Peserta Didik dalam Pembelajaran Matematika Kelas V UPTD SD Negeri 85 Parepare - Yonathan S Pasinggi; Abdul Halik; Nurul Annisa Asrul (MASALIQ, 2026)
The implementation of a learning model that encourages students’ active participation is necessary to improve mathematics learning outcomes, particularly in solid geometry. This study aims to analyze the effect of the Think Pair Share (TPS) cooperative learning model on fifth-grade students’ mathematics learning outcomes in solid geometry at UPTD SD Negeri 85 Parepare. The study employed a quantitative approach using a quasi-experimental method and a nonequivalent pretest-posttest control group design. The study population comprised all 68 fifth-grade students. The sample was determined using a saturated sampling technique, with 34 students from Class V.A assigned to the control group and 34 students from Class V.B assigned to the experimental group. Data were collected through a learning outcome test consisting of 15 multiple-choice questions administered at the pretest and posttest stages. The data were analyzed using descriptive and inferential statistics, including normality tests, homogeneity tests, and an independent-samples t-test. The results showed that the experimental group achieved a mean posttest score of 84.68, which was higher than the control group’s mean score of 77.65. The independent-samples t-test yielded a significance value of 0.001 ≤ 0.05; therefore, H₀ was rejected and H₁ was accepted. This study concludes that the TPS cooperative learning model has a positive and significant effect on fifth-grade students’ mathematics learning outcomes in solid geometry at UPTD SD Negeri 85 Parepare. These findings strengthen the application of cooperative learning as an alternative mathematics teaching strategy that promotes student engagement and improves learning outcomes.